PENINGKATAN HASIL BELAJAR BAHASA INDONESIA MELALUI METODE LATIHAN SISWA KELAS IV SD NEGERI 009 AIR EMAS KECAMATAN UKUI - Mulyani, Tri (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2016)
The background of this research is to learn Indonesian low yields, it is proved that out of 28students only 14 Siwa which reached KKM. To the researchers conduct classroom actionresearch with the aim to improve learning outcomes Indonesian. This research is a class actwho do sebanya two cycles by applying the method of exercise. This research was conductedin SD Negeri 009 Air Emas Kecamatan Ukui. The data used in this study is the activity dataand the teacher and student learning outcomes. Based on the research data showed that theactivities of teachers and students has increased at each cycle, as evidenced by getting ascore, namely: (a) the activities of teachers has increased in each cycle, the first cycle ofmeetings I gained a score of 9 (37.50%), the first cycle II meeting obtain a score of 14(58.33%), the second cycle of meetings I obtain a score of 19 (79.16%). And the second cycleII meeting obtain a score of 21 (87.50%). Additionally the activity of students has increased ateach cycle. At the meeting I cycle I obtained a score of 9 (37.50%), in the second meeting ofthe second cycle obtain a score of 16 (66.68%), at a meeting I cycle II obtained a score of 18(75.00%). And at the second meeting of the second cycle obtain a score of 22 (91.67%); and(b) the learning outcomes of students has increased at each cycle. In the first cycle thenumber of students who scored at intervals of> 80 amounted to 0 (0%), at intervals of 75-84value amounted to 7 students (25.00%), at intervals of 65-74 values were 12 students(42.85%) and at intervals of 55-64 value amounted to 9 students (32.14%). In the secondcycle the number of students who scored at intervals of> 80 amounted to 0 (0%), at intervalstotaling 21 students grades 75-84 (75.00%), at intervals of 65-74 grades are 5 students(17.85%) and at intervals of 55-64 value amounted to 2 students (7.14%). Additionallymastery learning students also increased, in the first cycle is the number of students whocompleted the 19 students (67.85%) increased in the second cycle by the number of 26students (92.85%).